2021
DOI: 10.3390/rs13050840
|View full text |Cite
|
Sign up to set email alerts
|

Normalized Difference Vegetation Index Temporal Responses to Temperature and Precipitation in Arid Rangelands

Abstract: Rangeland degradation caused by increasing misuses remains a global concern. Rangelands have a remarkable spatiotemporal heterogeneity, making them suitable to be monitored with remote sensing. Among the remotely sensed vegetation indices, Normalized Difference Vegetation Index (NDVI) is most used in ecology and agriculture. In this paper, we research the relationship of NDVI with temperature, precipitation, and Aridity Index (AI) in four different arid rangeland areas in Spain’s southeast. We focus on the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 46 publications
(58 reference statements)
2
12
2
Order By: Relevance
“…Our results reach the same conclusion, VCI and VHI showed greater values during the autumn and spring transition phases and achieved low stable values during winter and summer, when temperature and precipitation are limiting. Similar trends for MODIS NDVI were reported by [27,70], suggesting that NDVI is restricted, as well as grassland vegetation, during the summer and winter seasons.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our results reach the same conclusion, VCI and VHI showed greater values during the autumn and spring transition phases and achieved low stable values during winter and summer, when temperature and precipitation are limiting. Similar trends for MODIS NDVI were reported by [27,70], suggesting that NDVI is restricted, as well as grassland vegetation, during the summer and winter seasons.…”
Section: Discussionsupporting
confidence: 86%
“…Artificial intelligence has been used to measure drought episodes [25,26]. Even more, Sanz et al (2021) [27] related a cumulative AI with cumulative NDVI to characterize the efficient use of water resources in shorter periods than a year.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the present study, reports witnessed that NDVI change (either increasing or decreasing) is driven by precipitation/temperature in arid and semi-arid areas of Africa [128,129] and in other countries (i.e Spain, Iraq and China) of the world [94,[130][131][132][133]. NDVI controls the growth of vegetation conditions, temporal biomass accumulation, and changes [134].…”
Section: Trends Of Temporal and Seasonal Ndvicontrasting
confidence: 96%
“…In addition, long time series NDVI data directly reflects the vegetation growth status and has shown robust results to identify damaged vegetation [1,10]; however, the saturation property of NDVI posed a known weakness which limited the application of vegetation index in dense vegetation areas, and some scholars did not improve the sensitivity of NDVI conversion to vegetation components greater than 0.6 [40,41]; therefore, other scholars have proposed a remote sensing estimation method based on the combination of vegetation index and mixed pixel decomposition [3]. The pixel dichotomy model was widely selected to establish the transformation relationship between vegetation coverage and NDVI, because the vegetation coverage can not only indicate vegetation growth but also can describe surface vegetation in dense vegetation areas, so it can be used as an indicator for monitoring surface vegetation in the mining areas [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the dynamic trend of long time series data and regression analysis can describe the potential status of vegetation degradation more accurately [6,7]. MODIS NDVI and meteorological variables were selected to analyze the characteristics of seasonal or annual vegetation in different regions, and the trend analysis method was chosen to study the robustness 2 of 14 of regional vegetation change [1,[8][9][10]. Meanwhile, combined with higher resolution Landsat NDVI and the grey forecasting model can calculate and predict vegetation coverage better [11,12].…”
Section: Introductionmentioning
confidence: 99%